Research on usability of visualization in searching economic information in topic maps based application for return on investment indicator - Dudycz, Helena (Badanie użyteczności wizualizacji w wyszukiwaniu informacji ekonomicznej w aplikacji mapy pojęć do analizy wskaźnika zwrotu z inwestycji, 2011)
In business environment, where quick and reliable access to knowledge is crucial factor of success, efficient processing of data and information resulting in acquiring new knowledge concerning enterprise becomes essential. Research on using topic maps standard for the representation of knowledge about economic measures is conducted. Used visualization of the semantic network in topic map can provide valuable assistance for the economic data analysis and decision making tasks. The paper reports the results of an end-user study,which assessed the usability of visualizing semantic network based on topic maps to search information in application for return on investment (ROI) indicator. To achieve this goal, the usability testing technique and heuristic evaluation of user interface were used
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 45-58
Keywords: ontology of economic indicators; information visualization; evaluation of usability of visualizing in searching information; return on investment indicator; topic map